KONTRIBUSI MINAT KERJA TERHADA KESIAPAN KERJA SISWA PADA DUNIA INDUSTRI KELAS XI JURUSAN TEKNIK BANGUNAN SMK NEGERI 2 BENGKULU - 2069-2073, Emilyawinri (CIVED, 2018)
Abstract-The number of unemployment is expected to be relatively high for SMK graduates because SMK graduates not fully prepared for work.. When traced, student’s interested in SMKN 2 Bengkulu majoring civil is still low to work. Based on that fact, this experiment purposes to analysis the correlation about students interested to work and their readiness for work on industrial global of class XI majoring civil in SMKN 2 Bengkulu. Population in this analysis are students of civil majoring in SMKN 2 Bengkulu with total of 48 people using total sampling method. The analysis technique that we use are: 1) Descriptive analysis, 2) Requirement test analysis that consist of normality test and linearity test, and 3) Hypothesis test. Based on this analysis result, we could conclude there is a correlation between students interested to work and their readiness for work on industrial global of class XI majoring civil in SMKN 2 Bengkulu by 95% credibility. This can be seen from the coefficient value at 0.822, in the category of 0.80-1000 with a very strong relationship level.                                                                                                      Key Word: contribution, work interest, readiness of student work